2024
DOI: 10.1002/edn3.572
|View full text |Cite
|
Sign up to set email alerts
|

Improving the recovery for dissolved eDNA state: A comparative analysis of isopropanol precipitation, magnetic bead extraction, and centrifugal dialysis

Anish Kirtane,
Kristy Deiner

Abstract: Environmental DNA consists of multiple states including but not limited to membrane‐bound, adsorbed, and dissolved states. Because of their chemical and physical properties, each of these states may have different degradation and transport potential. Essential to the study of eDNA states is being able to isolate them from an environmental sample. Here, we focus on improving the DNA recovery of the dissolved state of eDNA from water. We compared three recovery methods, namely isopropanol precipitation, magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…However, lower DNA extraction efficiency should be expected with methods other than modern spin columns. In a comparison study [53], isopropanol precipitation reported DNA recovery of 52.47 ± 19.69% (see also [54]), centrifugal dialysis 12.58 ± 7.15%, and magnetic bead extraction 9.92 ± 3.89%, all notably lower than the above spin column efficiencies.…”
Section: Plasmid2mcmentioning
confidence: 94%
“…However, lower DNA extraction efficiency should be expected with methods other than modern spin columns. In a comparison study [53], isopropanol precipitation reported DNA recovery of 52.47 ± 19.69% (see also [54]), centrifugal dialysis 12.58 ± 7.15%, and magnetic bead extraction 9.92 ± 3.89%, all notably lower than the above spin column efficiencies.…”
Section: Plasmid2mcmentioning
confidence: 94%